Re-Enacting Ecosystems: Jakob Kudsk Steensen’s Environmental Storytelling in Virtual and Augmented Reality - Baldacci, Cristina (piano b. Arti e culture visive, 2021)
The paper intends to examine Jakob Kudsk Steensen’s environmental storytelling from the perspective of an art historian, and proposes re-enactment as a reading key to reflecting on the creative manipulation of time and space. Steensen’s virtual, augmented, and/or mixed reality installations, such as Aquaphobia (2017), Re-Animated (2018), The Deep Listener (2019), Berl-Berl (2021), permit an immersive experience of endangered ecosystems that the artist recreates – both doing field work and using 3D animation, gaming platforms, photography (photogrammetry), and sound design – either to sensitise public awareness of ecological issues or to pass on the memory of extinct landscapes and species – or both. His practice raises some important questions on which the paper will focus: How can designed simulated installations re-enact or even foresee and pre-enact an extinct ecosystem and delve into environmental issues? What are the psychological implications and changes in perception that such virtual experiences induce? What forms of consciousness and agency do they encourage?